A randomised trial of ondansetron for the treatment of irritable bowel syndrome with diarrhoea - Garsed, Klara; Chernova, Julia; Hastings, Margaret; Lam, Ching; Marciani, Luca; Singh, Gulzar; Henry, Amanda P.; Hall, Ian P.; Whorwell, Peter; Spiller, Robin C. (BMJ Publishing Group, 2013)
Background: Irritable bowel syndrome with diarrhoea (IBS-D) is particularly debilitating due to urgency and episodic incontinence. Some 5-hydroxytryptamine 3 (5-HT3) receptor antagonists (5-HT3RAs) have proven effective but have serious side effects. Ondansetron, also a 5-HT3RA, has been widely used as an antiemetic with an excellent safety record for over two decades. Our aim was to assess its effectiveness in IBS-D.